Butterfly Diversity (Lepidoptera) in The Kerandangan Nature Tourism Park Area - Pebrianti, Hasita; Naunik, Harsa; Agustini , Putu Linda; Hidayat, X Zardht Alex; Manisa, Safariyanti; Larasati, Sri Aprilia Nur; Permatasari , Dian Dwi; Kurniawan, Ramdani; Purnamawati, Rena; Umami, Lia (Yayasan Siti Widhatul Faeha, 2025)
Butterflies (order Lepidoptera) are a group of insects that have an important role in ecosystems as pollinators, part of the food chain, and bioindicators of environmental quality. The diversity of butterflies also contributes to the aesthetic value and ecotourism potential of an area. This study aims to identify the types of butterflies and analyze their diversity and abundance in the Kelantangan Nature Tourism Park (TWA), West Lombok, West Nusa Tenggara. The survey was conducted using the visual transect method along the observation path at the active time of the butterflies, namely morning and noon. Data were analyzed using the Shannon-Wiener diversity index (H'), the Simpson dominance index (D), and the uniformity index (E). The results of the study show that the TWA Kerandangan area has a moderate to high level of butterfly diversity, with several species classified as endemic and indicators of habitat quality. The existence of different types of host plants and natural vegetation supports the diversity of species found. These findings show the importance of the role of the TWA Kerandangan area as an insect habitat and support the urgency of sustainable conservation management. In addition, the results of this research can be used as a basis for the development of biodiversity-based educational ecotourism in the region.